2009
DOI: 10.1007/s10919-009-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Speech-Accompanying Gestures: Eye Movements and Information Uptake

Abstract: There is growing evidence that addressees in interaction integrate the semantic information conveyed by speakers' gestures. Little is known, however, about whether and how addressees' attention to gestures and the integration of gestural information can be modulated. This study examines the influence of a social factor (speakers' gaze to their own gestures), and two physical factors (the gesture's location in gesture space and gestural holds) on addressees' overt visual attention to gestures (direct fixations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
5
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 42 publications
11
85
5
5
Order By: Relevance
“…Previous studies analysed healthy subjects' visual exploration of co-speech gestures while observing an actor who was retelling cartoon stories. These studies found that gestures attract only a minor portion of attention (2e7%), while the speaker's face is much more fixated (90e95%) (Beattie, Webster, & Ross, 2010;Gullberg & Holmqvist, 1999, 2006Gullberg & Kita, 2009;Nobe, Hayamizu, Hasegawa, & Takahashi, 2000). To the best of our knowledge the visual exploration behaviour of co-speech gestures has not been studied in aphasic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies analysed healthy subjects' visual exploration of co-speech gestures while observing an actor who was retelling cartoon stories. These studies found that gestures attract only a minor portion of attention (2e7%), while the speaker's face is much more fixated (90e95%) (Beattie, Webster, & Ross, 2010;Gullberg & Holmqvist, 1999, 2006Gullberg & Kita, 2009;Nobe, Hayamizu, Hasegawa, & Takahashi, 2000). To the best of our knowledge the visual exploration behaviour of co-speech gestures has not been studied in aphasic patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible for a student to focus on a visual target (teacher) without paying attention to it (i.e. 'looking without observing') and, conversely, paying attention to something without directly focusing on it ('observing without looking') [18]. There is a very crucial and subtle difference between the two.…”
Section: Resultsmentioning
confidence: 99%
“…Although this may serve as an explanation for how accuracy rates were similar across conditions, it is important to note that the mechanisms behind gestural misinformation are not comparable with those of verbal misinformation. If nonverbal misinformation is incorporated into an eyewitness' representation, it occurs through a more covert process: gestures are not readily noticed in conversation (Gullberg & Holmqvist, 2002, 2006, even when fixated (Gullberg & Kita, 2009), and listeners often cannot identify gesture as the source of information retrospectively (Kelly et al, 1999). This is an important consideration to take into account because the success of gestures in manipulating memory reports could be attributed to a lack of source monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of verbal misinformation are mediated by source monitoring, gestures may not be subject to the same credibility assessments, as listeners do not subscribe to information conveyed by them overtly. Gestures are not often attended to in conversation (Gullberg & Holmqvist, 2002, 2006Gullberg & Kita, 2009) and listeners show little awareness of when information has been conveyed to them nonverbally: Kelly et al (1999) report that when presenting the sentence "my brother went to the gym" with a "shooting a basketball" gesture, listeners not only extracted the critical "basketball" information from gesture, but often remembered this as being part of speech. Thus, while gestures can convey information that carries the same semantic value as information in speech, they often provide listeners with this information without any trace of having done so.…”
mentioning
confidence: 99%